KEARIFAN LOKAL MENUJU PENGUATAN KARAKTER SOSIAL: SUATU TANTANGAN DARI KEMAJEMUKAN BUDAYA DI SUMATERA BARAT - Nursyirwan - Effendi (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2014)
This paper introduces a general understanding of local wisdom that may strengthen social identity to sustain social integrity in a plural society. Local wisdom may become a buzzword in modern societies where social and cultural diversity challenges the existence of society as a whole. West Sumatra Province deals with kind of social development where people from different ethnic groups background in Indonesia have already settled among local people in the provice. The Minangkabau, as people of origin and already enjoyed their majority, cannot avoid the pluralistic social interactions taking place in their own home land. Is this current social development sensitive? How local wisdom may play a role of avoiding social sensistivity?.  Results of this study show that plurality is unavoidablesocial consequences among Minangkabau people today and local wisdom become richer in terms of variations as before due to each community of different ethnic groups bringing it with them as long as living in the area of Minangkabau people. Hence the local wisdom may vary socal characteristics among communities. Main conclusion is local wisdom may play an important role of providing an alternative way of avoiding crisis of social integration in the context of west Sumatra province.